Penerapan Media Audio Visual (Vidio Animasi Kartun) Materi Wudhu Pada Mata Pelajaran Pendidikan Agama Islam Di Kelas I dan II SD IT Al-Mawaddah Warrahmah Kolaka - Annisa Annisa; Fatmawati Fatmawati; Hikmawati Hikmawati; Hikmayanti Hikmayanti; Rismayanti Rismayanti; Muh Aras; Amir Sahaka; Titi Meldawati; Nur Thahirah Umajjah (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
The use of media in classroom teaching is a necessity that cannot be ignored. The purpose of this study is: 1). Knowing the response of class I and II students of Elementary School Islamic Integrated (SD IT) Al Mawaddah Warrahmah Kolaka Against Audio Visual (video animation animation) in ablution material as a learning medium on subjects of Islamic religious education in terms of student learning motivation. 2) Knowing the application of audio visual media (cartoon animation video) in ablution material on subjects how Islamic religious education. 3) Knowing the teacher's response to audio-visual media (video animation video) in ablution material on subjects of Islamic religious in terms of learning motivation. The subjects of the trial were students who were respondents in a study, in this study the subject of the trial was students totaling 13 people. This research is located at Pondok Pesantren Street, Kolaka Regency. Research variables are component focal points in a study. In this study there are two research variables, namely: (1) Audio visual media (animated cartoon videos) and (2) student learning motivation. The conclusions that can be taken after conducting this research are as follows: 1). The response of students to audio visual learning media (cartoon animation video) in terms of learning motivation 100% very good. This means that around 100% of students can be motivated in using audio visual media (cartoon animation videos) on Islamic religious education subjects. 2) The application of this cartoon audio visual media, the first step is to prepare video procedures for ablution, prepare supporting tools. After the media is ready to be used, the researcher conducts the teaching and learning process by playing videos on the procedure of ablution while practicing it. 3) In the application of audio visual media (cartoon animation video) on Islamic religious education lessons in class I and II SD IT Al Mawaddah Warrahmah kolaka, the teacher responded well to this because this audio-visual media (cartoon animation video) is very suitable for use in class I students. and II, because they are very happy to play and watch.